Sex-determining Region Y-box transcription factor 13 promotes breast cancer cell proliferation and glycolysis by activating the tripartite motif containing 11-mediated Wnt/β-catenin signaling pathway. Issue 5 (2nd May 2022) - Jin, Xiaoyan; Shao, Xuan; Pang, Wenyang; Wang, Zhengyi; Huang, Jian
ABSTRACT: Breast cancer is the most frequent cancer among women and the second highest mortality in female across the world. Recent studies have illustrated that sex-determining region Y (SRY)-box protein (SOX) family plays essential roles in regulating various cancers. Nevertheless, the detailed effects of SOX13 on breast cancer are still uncovered. In our present study, SOX13 protein level was measured by using western blot assay in tissues and cells, and the results showed that SOX13 was upregulated in breast cancer tissues and cells compared with normal samples. Moreover, silencing SOX13 inhibited breast cancer cell viability, arrested cell cycle at G1/S phase and suppressed glycolysis, while overexpression of SOX13 reversed these events. Additionally, SOX13 knockdown reduced the level of proteins related to Wnt/β-catenin signaling pathway, whereas overexpression of tripartite motif containing 11 (TRM11) efficiently attenuated the effects, indicating that SOX13 controlled Wnt/β-catenin pathway depending on TRIM11. Furthermore, the data gained from xenograft tumor model illustrated that silencing SOX13 suppressed the tumor growth in nude mice and the glycolysis of tissues. In conclusion, our investigation illustrated that SOX13 facilitated breast cancer cell proliferation and glycolysis by modulating Wnt/β-catenin signaling pathway affected via TRIM11. Graphical abstract:This investigation revealed that SOX13 promoted breast cancer proliferation and glycolysis in vivo and in vitro . Additionally, SOX13 was able to regulate Wnt/β-catenin signaling pathway by mediating TRIM11 expression: uf0001